Soil nitrous oxide emissions in a maize (Zea mays L.) crop in response to nitrogen fertilisation - Alvarez, Carolina; Álvarez, Carina R.; Alves, Bruno J.R.; Costantini, Alejandro Oscar (CSIRO Publishing, 2024)
Context. An appropriate use of the fertiliser technology may lead to a more efficient N absorptionand to the reduction of economic and environmental costs. Aims. This study sought to quantify N2Oemissions generated from soil and the residual nitrate (NO3−) up to 2 m depth in field conditions in amaize crop under supplementary irrigation and fertilised with two nitrogen (N) sources (UAN andurea) at increasing N rates (0, 80, 160 and 250 kg N ha−1) in the Semi-arid Argentine Pampas.Methods. Throughout the crop cycle, emissions were monitored daily with static chambersduring the first week after fertilisation; then sampling frequency was gradually reduced until theend of the experiment. Key results. There were no yield responses to the use of differentsources and N rates. Crop N uptake saturated at 80 kg N ha−1, reaching 300–310 kg N ha−1.Residual NO3− increased significantly with the highest rates of N fertiliser. Total N2O emissionsdiffered significantly only among fertiliser rates. The N2O emissions were lower at 80 than at160 and 250 kg N ha−1. Conclusions. The N2O emissions measured were lower than thosecalculated by the IPCC, even when only direct emissions were considered. No grain yield increasewas observed due to N fertilisation, with a non-limiting supply of N-NO3− at the beginning of thecrop cycle and of N from mineralisation. Implications. This excess of N can generate negativeenvironmental effects due to higher emissions of N2O and residual N-NO3− that can be leached.